KEPEMIMPINAN INOVATIF KEPALA SEKOLAH DALAM MENDORONG TRANSFORMASI PEMBELAJARAN BERBASIS TEKNOLOGI UNTUK PENGUATAN KUALITAS PENDIDIKAN - Nur Efendi (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
This study aims to examine the role of innovative school leadership in promoting technology-based learning transformation to enhance educational quality. A qualitative approach with a case study design was employed at SMK Karya Dharma 1 Trenggalek. Data were collected through in-depth interviews, classroom observations, and document analysis. The findings reveal that the principal implements innovative leadership by strengthening a digital vision, facilitating teacher professional development, and fostering a collaborative culture that supports innovation. The transformation of learning is reflected in increased use of digital technologies, diverse instructional strategies, and higher student engagement. Classroom interactions become more dynamic and student-centered. Several challenges emerge, including disparities in teachers’ digital literacy, limited infrastructure, and resistance to change. The principal addresses these challenges through continuous training programs and strategic resource management. The study concludes that innovative leadership plays a significant role in improving the quality of technology-based education in vocational schools and supports sustainable transformation in learning practices.